2021
DOI: 10.3389/fpsyg.2021.729077
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Space With the “Victim” Can Increase Help Rates. A Study With Virtual Reality

Abstract: A typical protocol for the psychological study of helping behavior features two core roles: a help seeker suffering from some personal or situational emergency (often called “victim”) and a potential helper. The setting of these studies is such that the victim and the helper often share the same space. We wondered whether this spatial arrangement might affect the help rate. Thus, we designed a simple study with virtual reality in which space sharing could be manipulated. The participant plays the role of a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Further investigation is needed to better understand the specific factors that influence empathy in VR intergroup interactions. Supporting this notion (Rosenberg et al, 2013;Spagnolli et al, 2021), revealed that the use of humanoid avatars increased participants' propensity to help in moral decision-making scenarios. Collectively, these studies highlight the potential of EVAs to promote positive social norms and behaviours in interactions with VCs.…”
Section: Contexts and Applications Of Xr And Evas In Eliciting Prosoc...mentioning
confidence: 92%
See 2 more Smart Citations
“…Further investigation is needed to better understand the specific factors that influence empathy in VR intergroup interactions. Supporting this notion (Rosenberg et al, 2013;Spagnolli et al, 2021), revealed that the use of humanoid avatars increased participants' propensity to help in moral decision-making scenarios. Collectively, these studies highlight the potential of EVAs to promote positive social norms and behaviours in interactions with VCs.…”
Section: Contexts and Applications Of Xr And Evas In Eliciting Prosoc...mentioning
confidence: 92%
“…Of particular relevance, a study by (Spagnolli et al, 2021) demonstrated that co-location in VR positively influences prosocial behaviour. Participants sharing a VR environment with a virtual victim exhibited increased helping behaviour, regardless of the emergency type (plea for assistance or ongoing virtual fire).…”
Section: Contexts and Applications Of Xr And Evas In Eliciting Prosoc...mentioning
confidence: 99%
See 1 more Smart Citation